Perineuronal Nets in Spinal Motoneurones: Chondroitin Sulphate Proteoglycan around Alpha Motoneurones - Irvine, Sian F; Kwok, Jessica C F (International journal of molecular sciences, 2018)
Perineuronal nets (PNNs) are extracellular matrix structures surrounding neuronal sub-populations throughout the central nervous system, regulating plasticity. Enzymatically removing PNNs successfully enhances plasticity and thus functional recovery, particularly in spinal cord injury models. While PNNs within various brain regions are well studied, much of the composition and associated populations in the spinal cord is yet unknown. We aim to investigate the populations of PNN neurones involved in this functional motor recovery. Immunohistochemistry for choline acetyltransferase (labelling motoneurones), PNNs using Wisteria floribunda agglutinin (WFA) and chondroitin sulphate proteoglycans (CSPGs), including aggrecan, was performed to characterise the molecular heterogeneity of PNNs in rat spinal motoneurones (Mns). CSPG-positive PNNs surrounded ~70-80% of Mns. Using WFA, only ~60% of the CSPG-positive PNNs co-localised with WFA in the spinal Mns, while ~15-30% of Mns showed CSPG-positive but WFA-negative PNNs. Selective labelling revealed that aggrecan encircled ~90% of alpha Mns. The results indicate that (1) aggrecan labels spinal PNNs better than WFA, and (2) there are differences in PNN composition and their associated neuronal populations between the spinal cord and cortex. Insights into the role of PNNs and their molecular heterogeneity in the spinal motor pools could aid in designing targeted strategies to enhance functional recovery post-injury.
Keywords: Motor Neurons; Extracellular Matrix Proteins; Spinal Cord; Neuronal Plasticity; cholin-O-acetyltransferasa; extracelulární matrix; Chondroitin Sulfate Proteoglycans; krysa rodu Rattus; extracelulární matrix - proteiny; Animals; ženské pohlaví; mícha; zvířata; Extracellular Matrix; Rats; alpha motoneurone; perineuronal nets; chondroitinsulfát proteoglykany; gamma motoneurone; motorické neurony; chondroitin sulphate proteoglycans; Female; spinal cord; neuroplasticita; Choline O-Acetyltransferase